2021
DOI: 10.3758/s13428-020-01523-z
|View full text |Cite
|
Sign up to set email alerts
|

RealPic: Picture norms of real-world common items

Abstract: Pictures are often used as stimuli in several fields, such as psychology and neuroscience. However, co-occurring image-related properties might impact their processing, emphasizing the importance of validating such materials to guarantee the quality of research and professional practices. This is particularly relevant for pictures of common items because of their wide applicability potential. Normative studies have already been conducted to create and validate such pictures, yet most of them focused on stimulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
(203 reference statements)
0
10
0
1
Order By: Relevance
“…In recognition of this, there is increasing number of publications of normative ratings for icons and other pictorial stimuli that include ratings of aesthetics. In a recent review of normative studies of pictures, Souza et al ( 2020 ) argued that aesthetic appeal was an important stimulus characteristic and part and parcel of the cognitive processing of both pictures and icons (see also Garrido et al, 2016; McDougall & Reppa, 2008 ; Prada et al, 2016 ; Souza et al, 2021 ). Icon-specific research has also demonstrated the importance of these factors in determining user performance (Reppa et al, 2021 ; Reppa & McDougall, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recognition of this, there is increasing number of publications of normative ratings for icons and other pictorial stimuli that include ratings of aesthetics. In a recent review of normative studies of pictures, Souza et al ( 2020 ) argued that aesthetic appeal was an important stimulus characteristic and part and parcel of the cognitive processing of both pictures and icons (see also Garrido et al, 2016; McDougall & Reppa, 2008 ; Prada et al, 2016 ; Souza et al, 2021 ). Icon-specific research has also demonstrated the importance of these factors in determining user performance (Reppa et al, 2021 ; Reppa & McDougall, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The stimulus materials for the encoding manipulation consisted of 96 images of common items, selected from a normalized database (Souza et al, 2021). The original items belonged to eight well-studied superordinate categories (from Santi et al, 2015) from living (fruits, vegetables, mammals, birds) and non-living (vehicles, clothes, kitchen utensils, and musical instruments) domains rated on commonly reported dimensions in normative studies using such type of stimuli (Souza et al, 2020).…”
Section: Stimulimentioning
confidence: 99%
“…Barry et al, 1997;Dan-Glauser & Scherer, 2011;Gilhooly & Logie, 1980;Ito et al, 1998;Paivio et al, 1968;Spreen & Schulz, 1966;Snodgrass & Vanderwart, 1980;Snodgrass & Yuditsky, 1996). This is also the case for icons (McDougall et al, 1999;Prada et al, 2015;Reppa et al, 2008;Rodrigues et al, 2018;Souza et al, 2020Souza et al, , 2021. The present series of experiments sought to examine potential bias in subjective ratings of the visual, affective, and semantic properties of icons.…”
Section: Discussionmentioning
confidence: 95%
“…The methods employed to obtain icon ratings have their origins in subjective rating norms developed for words and pictures (e.g. Barry et al, 1997;Dan-Glauser & Scherer, 2011;Ito, Cacioppo, & Lang, 1998;Paivio et al, 1968;Spreen & Schulz, 1966;Gilhooly & Logie, 1980;Souza et al, 2021;Snodgrass & Vanderwart, 1980;Snodgrass & Yuditsky, 1996). Similar norms are available for icon corpora (Forsythe et al, 2017;McDougall, & Curry, & de Bruijn, O., 1999;Prada et al, 2015;Rodrigues et al, 2018;Souza et al, 2020).…”
mentioning
confidence: 99%